Socio-economic Analysis and the Study of Prevalence, Awareness, Treatment, Control and Risk Factors of Hypertension in Hospital Staff - Shakya, Samjhana; Bhattarai, J; Rawal, K; Kunwar, AR; Shakya, YR; Sharma, D (Nepalese Heart Journal, 2013)
Hypertension is an important public health challenge in the developing and the developed world alike. This worksite based descriptive cross-sectional study was undertaken in Sahid Gangalal National Heart Centre in 2010 with 50 subjects were recruited by multistage purposive cluster sampling. The primary aim of this descriptive cross-sectional study was to assess the socioeconomic status and to measure the prevalence, awareness, treatment, and correlates of hypertension. The prevalence of pre-hypertension is 38% and hypertension is 34%. Among the hypertensive 53% are aware of their condition and 66.66% of them are under treatment and 16.66% have control over the condition. The prevalence of overweight and obesity were 22% and 4% respectively. The prevalence of central obesity was 29.72% among male and 69% among female. Knowledge, Attitude and Practice on hypertension was satisfactory. Fourteen percent understood hypertension as a raised blood pressure during blood flow in the arteries. Majority of them (72%) have positive attitude towards use of medicine in hypertension. Majority of them (86%) had checked their blood pressure in last 2 years. Difference in prevalence of hypertension was found among the tobacco users and non- users (65% vs 40%), who do regular exercise and those who do not (28% vs. 38%) and sleep disturbance was higher among hypertensive than non-hypertensive (48% vs. 10%). Patients with Dislipidemia (32%) had higher prevalence of hypertension than those without Dislipidemia (44% vs 30 %) Similar finding were found between overweight participants (26%) and normal weight participants (46% vs 34%). The prevalence of hypertension is higher with the higher socio-economic status. Nepalese Heart Journal | Volume 7 | No.1 | November 2010 (special issue) | Page 15-19 DOI: http://dx.doi.org/10.3126/njh.v7i1.8496